Optimizing Structural Steel Spur Gear Design for Reduced Stress Concentrations in Industry 4.0 Using Finite Element Analysis - Agrawal, Anant Prakash; Ali, Shahazad; Tripathi, Naveen Mani; Kumar, Rajeev; Srivastava, Pulkit (Recent Patents on Mechanical Engineering, 2025)
The advent of Industry 4.0 has highlighted the importance of spur gears in power transmission across the automotive, aerospace, and marine industries. However, these gears are susceptible to failure due to bending and contact stresses from fatigue. Designing an involute gear profile presents challenges, particularly in managing tooth root stresses and avoiding interference. This study tackles these issues through comprehensive stress analysis, using modeling and FEM assessment. The focus is on evaluating bending stresses at critical locations and identifying strategies to reduce stress concentrations at the gear tooth root. By enhancing gear robustness, this research could contribute to potential patents in gear technology.BackgroundSpur gears are crucial for power transmission but often fail due to fatigue-induced stresses and design challenges at the tooth root.ObjectiveThis study aims to address spur gear design challenges through comprehensive stress analysis, using modeling and FEM to assess bending stresses and explore strategies to reduce stress concentrations at the tooth root.MethodsThe research uses SolidWorks and ANSYS for FEM analysis, focusing on bending stresses and exploring modifications in gear design using various materials for optimization.ResultsThe analysis shows strategic modifications to the gear's fillet radius and addendum can reduce stress at the tooth root by 38.26%, with stainless steel being the optimal material for enhanced gear strength.ConclusionThe study emphasizes strategic adjustments in fillet radius and addendum to reduce stress in spur gears, highlighting stainless steel's superior performance for optimized design and enhanced strength.
Keywords: Industry 4.0